2021
DOI: 10.1016/j.jhazmat.2021.126587
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 spread in a classroom equipped with partition – A CFD approach

Abstract: In this study, the motion and distribution of droplets containing coronaviruses emitted by coughing of an infected person in front of a classroom (e.g., a teacher) were investigated using CFD. A 3D turbulence model was used to simulate the airflow in the classroom, and a Lagrangian particle trajectory analysis method was used to track the droplets. The numerical model was validated and was used to study the effects of ventilation airflow speeds of 3, 5, and 7 m/s on the dispersion of droplets of different size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 44 publications
(51 reference statements)
0
65
0
Order By: Relevance
“…The CFD analysis model used in this study was the transition SST k - ε model. Mirzaie et al [20] analyzed the effect of installing transparent barriers in front of classroom seats in order to prevent the effect of coughing or sneezing of a COVID-19 infected person standing in the front area of the classroom. It was observed that the barriers were quite effective for preventing the infection.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD analysis model used in this study was the transition SST k - ε model. Mirzaie et al [20] analyzed the effect of installing transparent barriers in front of classroom seats in order to prevent the effect of coughing or sneezing of a COVID-19 infected person standing in the front area of the classroom. It was observed that the barriers were quite effective for preventing the infection.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic, caused by the transmission of the SARS-CoV-2 virus, has claimed more than 3.88 million lives with more than 178.8 million people known to be infected worldwide ( World Health Organization (WHO) and Coronavirus, 2021 ) (at the time of writing in June 2021). As part of the international effort to combat COVID-19, researchers have employed computational modelling techniques to assess the potential efficacy of non-pharmaceutical mitigation strategies for a range of indoor environments ( Ronchi and Lovreglio, 2020 , Vuorinen et al, 2020 , Malki-Epshtein et al, 2020 , Marcus LJ, et al, Assessment of Risks of SARS-CoV-2 Transmission During Air Travel and Non-Pharmaceutical Interventions to Reduce Risk, Phase One Report: Gate-to-Gate Travel Onboard Aircraft., 2020 , Buonanno et al, 2020 , Rencken et al, 2021 , Zhang et al, 2021 , Li et al, 2021 , Mirzaie et al, 2021 ). An issue of societal concern is the possibility of contracting COVID-19 while confined to the small volume of the passenger compartment of a train carriage (saloon), where passengers are seated in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…The Lagrangian approach has also been applied to applications concerning infectious disease transmission ( Vuorinen et al, 2020 , Mirzaie et al, 2021 , Wang et al, 2014 , Peng et al, 2020 , Yan et al, 2017 , Zhang and Li, 2012 , Yang et al, 2018 ). As the Lagrangian approach treats the discrete respiratory aerosol particles as a collection of droplets that are individually tracked through space, it is necessary to specify the initial droplet size distribution, composition and thermodynamic properties – which are not necessarily known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient simulations have been conducted to simulate cough jets because the cough flow rate is time-dependent [ 13 , 14 , 15 ]. Mirzaie et al [ 16 ] conducted a numerical simulation of cough droplet dispersion for an infected person in front of a classroom. They found that droplet concentration was lower with higher ventilation rate and the partitions installed in front of the seats.…”
Section: Introductionmentioning
confidence: 99%